2008
DOI: 10.1111/j.1538-7836.2008.03168.x
|View full text |Cite
|
Sign up to set email alerts
|

Some hemostasis variables at the end of the population distributions are risk factors for severe postpartum hemorrhages

Abstract: Summary. Background: Severe postpartum hemorrhages (PPH) represent a significant cause of maternal morbidity/ mortality, but little is known about its hemostasis-related risk factors. Among the 32 463 women enrolled in the NOHA First cohort, 317 developed severe PPH (S-PPH group), 1269 nonsevere PPH (NS-PPH group) and the remaining individuals were considered as control women (C group). Methods: We performed a case-control study, including 317 triplets of women allocated from the three groups that shared the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 25 publications
4
37
1
2
Order By: Relevance
“…28 A case-control study of 317 women who developed severe postpartum hemorrhage demonstrated a correlation with low (but not abnormal) levels of fibrinogen, von Willebrand antigen and other factors including FXI. 29 In von Willebrand disease the bleeding tendency may be related to the number of collagen receptors on platelets as determined by gene polymorphisms. 30 It is likely therefore that the mild bleeding risk in FXI deficiency may be affected by minor changes in other components of the hemostatic pathways.…”
Section: Clinical Presentation and Managementmentioning
confidence: 99%
“…28 A case-control study of 317 women who developed severe postpartum hemorrhage demonstrated a correlation with low (but not abnormal) levels of fibrinogen, von Willebrand antigen and other factors including FXI. 29 In von Willebrand disease the bleeding tendency may be related to the number of collagen receptors on platelets as determined by gene polymorphisms. 30 It is likely therefore that the mild bleeding risk in FXI deficiency may be affected by minor changes in other components of the hemostatic pathways.…”
Section: Clinical Presentation and Managementmentioning
confidence: 99%
“…Nonetheless, it is possible that maternal conditions, not necessarily related to pregnancy, may enhance the risk of bleeding in these pregnancies. For instance, the mother may have an underlying bleeding disorder that will increase her risk of excess postpartum haemorrhage 16 and simultaneously cause a disproportional placental weight to birthweight ratio. It is also possible that certain pregnancy complications may initiate enlargement of the placenta relative to the fetus, and simultaneously deactivate the maternal clotting system.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with biventricular assist device implantation on treatment with clopidogrel, the strict monitoring of impaired platelet function with this method (by using CADP cartridge) allowed them to go under successful transplantation with no major blood loss [112] . Prolonged CTs by CADP assay were found be independent risk factors for post-partum hemorrhage (PPH) severity [113] and prolonged CTs by CADP cartridge have been consistently described to be correlated in women with menorrhagia [114] . The presurgical correction of the prolonged PFA-100 CT with DDAVP treatment, allowed to maintain the number of postoperative blood transfusions not significantly different from that of patients with normal presurgical PFA CT [106] .…”
Section: Platelet Function Point-of-care Testingmentioning
confidence: 99%
“…Hayward et al [25] Favaloro [94] Koessler et al [92] Marcucci et al [103] Reny et al [104] Crescente et al [105] Raman et al [108] Cammerer et al [109] Chauleur et al [113] VerifyNow system Assessment of: (1) residual platelet reactivity of patients on antiplatelet treatment to stratify risk of ischemic events; (2) low platelet reactivity of patients on antiplatelet treatment to stratify risk of bleeding events (scarce clinical data).…”
Section: Platelet Aggregation On Platelet-rich Plasmamentioning
confidence: 99%